Ідентифікація типу сорту хмелю звичайного за молекулярними маркерами генів, що кодують халконсинтази - Венгер, А.М.; Волкова, Н.Е. (Фактори експериментальної еволюції організмів, 2014)
Aims. Hop Humulus lupulus is a commercial important plant in Ukraine. The primary commercial application of the hop plants has been in the beer brewing industry. Most important substances from hop are bitter acids. Depending on level of bitter acids hop varieties derive in aroma and bitter. The purpose of present work was to study the possibility of hop types identification according to polymorphism of chs_H1, chs2, chs3, chs4 and vps genes in sampling of 20 Ukrainian hop varieties. Methods. Cluster analysis of hop type varieties was derived by analysis of gene polymorphism using UPGMA. Reliable was calculated by Spearman coefficient. Results. The cluster analyses of 20 Ukrainian hop varieties based on gene polymorphism data resulted in pure differentiation of studied varieties into bitter and aroma clusters. Conclusions. Dependence between chs_H1, chs2, chs3, chs4 and vps genes polymorphism and type of hop variety was shown. The method of type identification of hop varieties by molecular markers was developed. The elaborated method is statistically reliable and does not need much time or expensive reagents.